Why Work with Undergraduate Researchers? Differences in Research Advisors’ Motivations and Outcomes by Career Stage - Hayward, Charles N. (CBE Life Sci Educ, 2017)
Undergraduate research is often hailed as a solution to increasing the number and quality of science, technology, engineering, and mathematics graduates needed to fill the high-tech jobs of the future. Student benefits of research are well documented but the emerging literature on advisors’ perspectives is incomplete: only a few studies have included the graduate students and postdocs who often serve as research advisors, and not much is known about why research advisors choose to work with undergraduate researchers. We report the motivations for advising undergraduate researchers, and the related costs and benefits of doing so, from 30 interviews with research advisors at various career stages. Many advisors stated intrinsic motivations, but a small group of early-career advisors expressed only instrumental motivations. We explore what this means for how advisors work with student researchers, the benefits students may or may not gain from the experience, and the implications for training and retaining research advisors who can provide high-quality research experiences for undergraduate students.